Sources of social support and selected ways of coping among women with postpartum depression’ symptoms - Kossakowska, Karolina (Nursing Problems / Problemy Pielęgniarstwa, 2012)
Introduction. Childbirth and childcare, are related to adjusting to various changes, affecting a woman’s life and the whole family. Women who fall into postnatal depression symptoms, are also obliged to fight the disease. Important role in coping with stress which carries maternity, as well as with the symptoms of the disease — plays the assistance which the woman receives from the their environment, including members of the medical staff. Aim of the study. Evaluation the differences in the level of satisfaction with received support and ways of coping among women with and without symptoms of postpartum depression symptoms, as well as, determine the relationship between satisfaction with received support from various sources and the methods used by women dealing with symptoms of postpartum depression. Material and methods. 197 in 4–12 weeks postpartum were examined in the study: 113 women without symptoms of postpartum depression and 84 women suffering from postpartum depression. The following methods were used to find answers to the research questions: Edinburgh Postnatal Depression Scale (EPDS), COPE questionnaire and the scale for measuring social support. Results. Women experienced symptoms of postpartum depression reported greater satisfaction with support provided by midwives rather than from family members. Depressive women chose less active ways of coping. At the same time, the more they were satisfied with received social support, they were more likely to take active strategies. Conclusions. Social support is an important value for women with postpartum depression symptoms. Midwife, as a member of the medical staff remaining in the immediate relationship with a woman adapting to motherhood, may play an important role in coping by women with symptoms of mood disorders after giving birth.